The Wide Variety of Acute Disseminated Encephalomyelitis in Children: A Clinical Perspective - Hyunsuk Lim; Su-Kyeong Hwang; Yun-Jeong Lee; Soonhak Kwon (Korean Child Neurology Society, 2022)
Acute disseminated encephalomyelitis (ADEM) is an acute demyelinating inflammatory disorder of the central nervous system. It is characterized by encephalopathy, multifocal neurological deficits, and typical magnetic resonance imaging findings of widespread demyelinating lesions, predominantly involving the white matter of the brain and spinal cord. ADEM mainly affects children and is commonly associated with preceding viral and bacterial infections, and, rarely, vaccinations. Despite substantial advances in the understanding of the association of myelin oligodendrocyte glycoprotein antibody with recurrent forms of ADEM or other demyelinating conditions, specific etiologic agents or biological markers have not been identified. Therefore, the diagnosis of ADEM is still based on clinical and radiological findings and the exclusion of other conditions mimicking ADEM. However, a prompt diagnosis and adequate treatment are crucial because diagnostic delays or inappropriate treatment may lead to unwanted neurological sequelae in some children. There is no standardized treatment protocol for ADEM, but the use of corticosteroids, intravenous immunoglobulin, and plasmapheresis has been associated with good clinical outcomes. Adequate treatment has reportedly resulted in favorable outcomes, with full or almost full recovery in most children with ADEM, although some children may develop neurological sequelae, such as cognitive impairment and motor deficits. Further studies are needed to identify biological clues and optimal treatment protocols to minimize the incidence of neurological sequelae.